HeartMate 3 left ventricular assist device implant after excision of a large apical aneurysm - Chamogeorgakis, Themistokles (Proc (Bayl Univ Med Cent), 2020)
The presence of a left ventricular apical aneurysm may pose a technical challenge during implantation of a left ventricular assist device (LVAD). We describe implantation of a HeartMate III LVAD under cardioplegic arrest. A ventricular aneurysmectomy was performed and the LVAD was implanted at the left ventricular apex at the level of the transition zone between the scar tissue and the viable myocardium. Two pursestring 2-0 Prolene Fontan sutures were placed circumferentially at the transition zone to make up for the size discrepancy between the left ventricular opening and the HeartMate 3 pump. The echocardiographic analysis demonstrated optimal inflow cannula orientation, and the patient had an uneventful recovery.